Validating the visceral sensitivity index in an eating disorder sample. Issue 6 (15th January 2021) - Brown, Tiffany A.; Reilly, Erin E.; Murray, Helen Burton; Perry, Taylor R.; Kaye, Walter H.; Wierenga, Christina E.
Abstract: Objective: Individuals with eating disorders (EDs) often have difficulty tolerating uncomfortable body sensations. As such, anxiety sensitivity specific to gastrointestinal (GI) sensations, has relevance for EDs. However, to date, no validated measures of this construct exist in EDs. Thus, the present study sought to validate the visceral sensitivity index (VSI), a 15‐item measure originally validated in an irritable bowel syndrome sample, in an ED sample and explore associations with ED symptoms. Method: Two hundred and sixty‐six adolescents ( n = 116) and adults ( n = 150) in an ED partial hospital program completed the VSI and related measures at admission. Confirmatory factor analysis examined the factor structure of the VSI and hierarchical regression analyses explored associations between the VSI and ED symptoms. Results: The original version of the VSI had adequate model fit. An alternative 13‐item model removing specific items with poor fit and less theoretical relevance to EDs also demonstrated good fit. The 15‐item and 13‐item VSI had strong internal consistency ( α = .93–.94), and correlation results supported the convergent and divergent validity of both versions. Higher visceral sensitivity was associated with elevated body dissatisfaction, cognitive restraint, purging, restricting, and excessive exercise ( p ‐values <.05), beyond length of illness, body mass index, and trait anxiety. Discussion: Results support the relevance of GI‐specific anxiety in EDs and suggest that the original 15‐item VSI and modified 13‐item VSI have strong psychometric properties in an ED sample. Given comparable model fit and psychometric properties, both versions of the VSI may be used for future ED research.